Pengaruh Lama Pelapukan Media Limbah Industri Teh Terhadap Pertumbuhan Miselium Produksi Jamur Kuping Hitam (Auricularia polytrica (Mont.) Sacc.) - Mitra Angelia; - Periadnadi; - Nurmiati (Jurnal Biologi Universitas Andalas, 2013)
The study about effect of media composting duration from industrial waste of tea production to the mycelium growth and production of black ear mushroom (Auricularia polytrica (Mont.) Sacc.) was conducted from December 2012 to February 2013 in the Laboratory of Microbiology, Department of Biology, Andalas University, Padang. This study aimed to determine the effects of media composting duration to the mycelium growth and production of black ear mushrooms. The research was designed by using completely randomized design (CRD) in five treatments of Composting duration, they were 0, 1, 3, 5 and 7 days in 5 replications. The result showed that the treatment of 5 days media composting was the optimum length of time for 32 days the growth of mycellium, the weight of fruiting bodies was 50.89 g, the widest diameter of the cap of fruiting body was 9.05 cm, the cellulase activity of the mycellium in the baglogs was 4,769 units/g and producing the highest content of glucose after composting was 153.526 µg/g. Keywords: composting duration, waste of tea, Auricularia polytrica, mycelium growth.